Development of DNA Markers From Physically Mapped Loci in Aegilops comosa and Aegilops umbellulata Using Single-Gene FISH and Chromosome Sequences - Said, Mahmoud; Holušová, Katerina; Farkas, András; Ivanizs, László; Gaál, Eszter; Cápal, Petr; Abrouk, Michael; Martis-Thiele, Mihaela M.; Kalapos, Balázs; Bartoš, Jan; Friebe, Bernd; Doležel, Jaroslav; et al. (Frontiers in Plant Science, 2021)
Breeding of agricultural crops adapted to climate change and resistant to diseases and pests is hindered by limited gene pool due to domestication and many thousands of years of human selection. One way to increase the genetic variation is chromosome-mediated-gene-transfer from wild relatives by cross hybridization. In case of wheat (Triticum aestivum), the species of genus Aegilops are particularly attractive source of new genes and alleles. However, during the evolution of Aegilops and Triticum genera, diversification of D-genome lineage resulted in the formation of diploid C, M and U genomes of Aegilops. The extent of structural genome alterations, which accompanied their evolution and speciation, and the shortage of molecular tools to detect Aegilops chromatin hampers gene transfer into wheat. To investigate the chromosome structure and help developing molecular markers with known physical position that could improve the efficiency of the selection of desired introgressions, we developed single-gene FISH maps for M- and U-genome progenitors, Ae.comosa and Ae.umbellulata, respectively. Forty-three ortholog genes were located on 47 loci in Ae.comosa and on 52 loci in Ae.umbellulata using wheat cDNA-probes. The results obtained showed that M-genome chromosomes preserved collinearity with those of wheat, excluding 2M and 6M containing an intrachromosomal rearrangement and paracentric inversion of 6ML, respectively. While Ae.umbellulata chromosomes 1U, 3U and 5U maintained collinearity with wheat, structural reorganizations in 2U, 4U, 6U and 7U suggested a similarity with the C genome of Ae. markgrafii. To develop molecular markers with exact physical positions on chromosomes of Aegilops, the single-gene FISH data were validated in silico using DNA sequence assemblies from flow-sorted M- and U-genome chromosomes. The sequence similarity search of cDNA-sequences confirmed 44 out of the 47 single-gene loci in Ae. comosa and 40 of the 52 map positions in Ae. umbellulata. Polymorphic regions thus identified enabled development of molecular markers, which were PCR validated using wheat-Aegilops disomic chromosome addition lines. The single-gene FISH-based approach allowed development of PCR markers specific for cytogenetically mapped positions on Aegilops chromosomes, substituting as yet unavailable segregating map. The new knowledge and resources will support the efforts introgression of Aegilops genes into wheat and their cloning.